Pasantía: Transportadora Comercial Colombiana TCC (2022)
The company Transportadora Comercial Colombiana S.A, dedicated to the area of ground transportation and logistics, was founded in 1968 by Mr. Jorge¿ Agudelo Restrepo and Mrs. Rosalba Trujillo, during the year 1970 began their growth in the city of Bogotá being the beginning of its positioning in the Colombian market.